Hipertensi sebagai prediktor kejadian kardiovaskular mayor pada pasien infark miokard akut pada tahun 2018 di RSUP Sanglah Denpasar, Bali-Indonesia - A A Ayu Kaivalya Kirthi; A. A. Ayu Dwi Adelia Yasmin; I Made Junior Rina Artha; Agha Bhargah (DiscoverSys Inc., 2019)
Introduction: Acute Myocardial Infarction (AMI) is a leading cause of morbidity and mortality in developed countries, as well as emerged as a very important health problem in developing countries. Despite of management and treatment of AMI strategies has been evolving. Complications due to AMI cause high morbidity and mortality. To minimalize complications in AMI patients need some risk stratification. Risk stratification have been made based on AMI pathophysiology. Hypertension is a factor that directly influences the development of atherosclerosis through mechanical stress.Method: This study was a retrospective cohort observational study that enrolled 70 patients with AMI as the subject of research by consecutive sampling from January 2018 – September 2018. Data retrieval is done by taking data from medical records of patients in the Sanglah General Hospital. Outcome observed was in-hospital MACE (cardiovascular death, cardiogenic shock, heart failure, and malignant arrhythmias).Result: In this study, it was found that hypertension is a predictor of major cardiovascular events by almost 5-fold (HR = 5,02, 95% CI = 1,32-19,20, p = <0.018in patients with AMI that were treated at Sanglah General Hospital.Conclusion: The conclusion of this study is hypertension is a predictor of major cardiovascular events in patients with AMI on admission to hospital. The results of this study are expected to be used as baseline data for subsequent larger studies.